(untitled) (Proceedings of International Conference on BioScience and Biotechnology, 2017)
Coconut coir is composed of cellulose, lignin, pectin, and hemicellulose. Production of biofuels is one possible application of this lignocellulosic waste. Physical-chemical pretreatment is required in order to remove lignin and to increase cellulose digestability. Commonly, the coconut coir was pretreated primarily with NaOH solution (5-11%) in autoclave at 121°C for 1 hour. The aims of this work were to find an enhanced pretreatment procedure for the coconut coir, and to study kinetics of the cellulose hydrolysis process at elevated temperature. For this purpose, we used NaOH solution (5% w/v) and ultrasonic bath for 1 hour at 50°C, which can successfully replace autoclave pretreatment. Moreover, the temperature of the ultrasonic pretreatment coincided with the temperature of hydrolysis reaction carried out subsequently. Two commercial enzymes cellulase and β-galactosidase were applied simultaneously as biocatalyst for the enzymatic hydrolysis of cellulose. One of the advantages of the ultrasound-assisted pretreatment was the lowest weight loss of the coir - 48% (w/w). When using autoclave, the weight loss was much higher - about 66-67% (w/w) of the coir samples. First order kinetic equation for the enzymatic hydrolysis of cellulose to glucose was derived, and kinetic constants were obtained for the product released at different modes of operation.